Effect of harmonics In laboratory equipments - Mohd Hanif Abd Hadi (Universiti Malaysia Perlis, 2009)
This report, entitled “Effect of Harmonics in Laboratory Equipments” summarizes apart of final year project for the Electrical System engineering courses done in University Malaysia Perlis. This project is about learning how the harmonics (distortion) can effect the laboratory equipments especially for power supply, oscilloscope and pc (personal computer). Harmonic is a sinusoidal component of a waveform that has frequencies that are some multiple of the fundamental frequency of waveform. By using the harmonic analyzer (pm 300), the data for current and voltage harmonic can be taken. From the data, the solution for total harmonic distortion (THD) can be done by calculation.